RELATIONSHIPS AMONG THE CROWN DIMENSIONS AND THE HEIGHT OF DOMINANT TREES IN STANDS OF Pinus taeda L. - Padoin, Veridiana (2010)
Aiming at describing and modeling the morphometric relationships among the crown diameter, the crown percentage, the length of the crown exposed to light and the height of the dominant trees in stand of Pinus taeda L., one hundred and eighty seven sample units were studied considering the type proposed by Prodan, modified for twelve trees, distributed on good and bad stands. In each sample unit, two dominant trees were identified and the dimensions of the diameter at breast height, the total height, the crown lengths and the length of crown exposed to light and the crown diameter under eight rays were measured. Results allowed concluding that the crown diameter and the length of the crown exposed to light grow with the increase of the dominant height, and the two relationships can be described with good statistical precision by a curvilinear mathematical model. The relationship of the crown percentage with the dominant height presented high statistical significance described by a decreasing curvilinear model, having been identified by analysis of covariance three different groups of curves according to the place of origin of the data. The crown percentage decreases with the increase of the dominant height.